Analysis of Deviant Behavior of Class X Students at SMA Muhammadiyah Maumere - Kudara, Andiriani; Kepalet, Petrus; Natsir, H. Rodja Abdul (Lembaga Riset Mutiara Akbar, 2022)
Deviant behavior of adolescents or students can also be referred to as juvenile delinquency, which is an act that violates norms, rules or laws in society that is carried out at a young age or during the transition between childhood and adulthood. Juvenile delinquency in the study of social problems can be categorized into deviant behavior. deviant behavior that often occurs in class X students is individual deviation such as stubbornness including dating at school, being late), skipping school, skipping class and smoking in the school toilet. The research results obtained from several informants that there are several causal factors that influence deviant behavior by students due to several factors including